Boundaries of love : interracial marriage and the meaning of race - Osuji, Chinyere K. (New York : New York University Press, 2019)
"Osuji's "Boundaries of Love" explores the issues of race and interracial marriage"--
Introduction : race-mixing and ethnoracial boundaries -- Preferences and the romantic career -- Boundaries of blackness : groupness and linked fate -- Boundaries of whiteness : flexibility and shifting meanings -- Black, white, mixed or biracial : identifying the children -- "A fly in the buttermilk": black spouses in white families -- Policing the boundary : interacting with strangers in public -- Conclusion : "Is interracial love saving America?"
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 29, 2024).
JSTOR
Keywords: Čubrilović -- Familie : 19. Jh.-; Interracial marriage -- United States -- Case studies; Interracial marriage -- Brazil -- Case studies; Multiracial families -- United States -- Case studies; Multiracial families -- Brazil -- Case studies; Mariage interracial -- États-Unis -- Études de cas; Mariage interracial -- Brésil -- Études de cas; Familles métissées -- États-Unis -- Études de cas; Familles métissées -- Brésil -- Études de cas; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Interracial marriage; Multiracial families; Brazil; United States; Interkulturalität; Partnerschaft; Brasilien; USA; Familles mixtes -- États-Unis -- Los Angeles (Calif.); Familles mixtes -- Bresil -- Rio de Janeiro (Bresil); Mariage interethnique -- États-Unis -- Los Angeles (Calif.); Mariage interethnique -- Bresil -- Rio de Janeiro (Bresil); Electronic books; Case studies; Case studies; Études de cas